HUBUNGAN ANTARA BEBAN KERJA DENGAN STRES KERJA PADA PERAWAT RUMAH SAKIT DI INDONESIA - Rafika Alawiyah; Susilawati Susilawati (CV. ADIBA ADISHA AMIRA, 2023)
The workload on nurses needs to be considered so that there is no excessive burden that can cause stress on nurses. Job stress is a condition of tension that causes physical and psychological imbalances that can affect an individual's ability to deal with the environment. Furthermore, various symptoms of stress develop including physical, emotional and behavior that can interfere with work. The purpose of this study was to analyze the relationship between workload and work stress in hospital nurses in Indonesia. The research method used is systematic literature review which is used to identify, evaluate, and interpret all relevant research results related to this research. Researchers searched for relevant articles through Google Scholar. The results of this study are 5 relevant articles which state that workload has an influence on work stress in hospital nurses.